2019
DOI: 10.1183/13993003.01257-2018
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids and the risk of lung cancer in COPD: a population-based cohort study

Abstract: Inhaled corticosteroids (ICSs) are often prescribed in patients with chronic obstructive pulmonary disease (COPD). Their impact on the risk of lung cancer, a leading cause of mortality in COPD patients, remains uncertain.Population-based linked administrative data between the years 1997 and 2007 from the province of British Columbia, Canada, were used to evaluate the association between lung cancer risk and ICS use in COPD patients. COPD was defined on the basis of receipt of three COPD-related prescriptions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 34 publications
2
49
0
1
Order By: Relevance
“…48 Interestingly, previous studies reported that ICS use reduced the risk of lung cancer by 21% in the general population, 24 by 56% in patients with asthma, 25 and by 30% in patients with COPD. 26 We also found that ICS use reduced the risk of lung cancer by 56% in patients with asthma. These results may be explained by the ICS-mediated reduction of local inflammation.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…48 Interestingly, previous studies reported that ICS use reduced the risk of lung cancer by 21% in the general population, 24 by 56% in patients with asthma, 25 and by 30% in patients with COPD. 26 We also found that ICS use reduced the risk of lung cancer by 56% in patients with asthma. These results may be explained by the ICS-mediated reduction of local inflammation.…”
Section: Discussionmentioning
confidence: 58%
“…The cumulative ICS dose was calculated as the total dose of prescribed ICS medication and converted to fluticasone-equivalent dosages for comparison of different types of ICSs. 26 Atopic asthma was defined as asthma with 1 more atopic disorder (allergic rhinitis or atopic dermatitis), and nonatopic asthma as asthma without any atopic disorder. 31…”
Section: Nhis-nsc Full Unmatched Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the European Respiratory Journal, the study by RAYMAKERS et al [7] contributes to a growing body of scientific evidence in favour of lung cancer chemoprevention with ICS. RAYMAKERS et al [7] analysed a large population-based cohort of COPD patients and found that exposure to ICS in a sample of almost 40 000 individuals was associated with a 30% reduction in lung cancer risk (HR 0.70 (95% CI 0.61-0.80)). Their conclusion persisted after using five different time-dependent methods of quantifying exposure.…”
mentioning
confidence: 99%
“…Many validated inflammation indicators are linked to lung cancer risk; these include the use of corticosteroids, chronic obstructive pulmonary disease (COPD) and chronic pulmonary infection, even when smoking was ruled out . Our previous study also analysed 10 widely evaluated inflammatory biomarkers and noted an independent association between BLC and significant risk for early‐stage lung adenocarcinoma .…”
Section: Discussionmentioning
confidence: 99%